Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1177/1550059420934590
|View full text |Cite
|
Sign up to set email alerts
|

Localizing the Primary Motor Cortex of the Hand by the 10-5 and 10-20 Systems for Neurostimulation: An MRI Study

Abstract: Background. The primary motor cortex of the hand (M1-Hand) is a target used in transcranial magnetic stimulation (TMS) and in transcranial direct current stimulation (tDCS) for the treatment and evaluation of motor neurological diseases. Magnetic resonance imaging–guided neuronavigation locates the M1-Hand with high precision, but at a high cost. Although less accurate, the C3/C4 points of the international 10-20 system (IS 10-20) are routinely used to locate the M1-Hand. The international 10-5 system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 40 publications
(72 reference statements)
2
26
0
Order By: Relevance
“…For this reason, when targeting the primary motor cortex (M1), TMS stimulation parameters (position, angle, intensity) are initially set based on coarse a priori anatomical information (Silva et al, 2020) and then adjusted post-hoc, until the electromyographic (EMG) activity recorded from a selected target muscle satisfies standard latency and amplitude requirements (Rossini et al, 2015). Hence, despite the potential confound represented by changes in the excitability of spinal motor neurons, EMG waves as a real-time feedback have been the fundamental guide for titrating TMS in research, diagnostic and treatment protocols.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, when targeting the primary motor cortex (M1), TMS stimulation parameters (position, angle, intensity) are initially set based on coarse a priori anatomical information (Silva et al, 2020) and then adjusted post-hoc, until the electromyographic (EMG) activity recorded from a selected target muscle satisfies standard latency and amplitude requirements (Rossini et al, 2015). Hence, despite the potential confound represented by changes in the excitability of spinal motor neurons, EMG waves as a real-time feedback have been the fundamental guide for titrating TMS in research, diagnostic and treatment protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Channel 24 was located between C2 and C4 in the international 10/20 system and corresponded to (x = 42, y = – 21, z = 62) in MNI co-ordinates ( Morais et al, 2018 ). This channel was considered the primary motor cortical region related to hand movement among the four ROI channels, as the MRI study reported that the M1-Hand region was located between C2 and C4 ( Silva, Silva, Lira-Bandeira, Costa-Ribeiro, & Araújo-Neto, 2020 ). The results of this study give insight for selecting the target site for neuromodulation of stroke patients.…”
Section: Discussionmentioning
confidence: 99%
“…ordinates (Morais et al, 2018). This channel was considered the primary motor cortical region related to hand movement among the four ROI channels, as the MRI study reported that the M1-Hand region was located between C2 and C4 (Silva, Silva, Lira-Bandeira, Costa-Ribeiro, & Araújo-Neto, 2020 (Scholkmann, Gerber, Wolf, & Wolf, 2013). However, we could not apply this in our study due to a lack of short SDS 511 signals.…”
mentioning
confidence: 99%
“…showed the highest activation (Fig. 8), which are located around C4 (or C3) that is known to be the area responsible for hand movement [36]. MT induced activation on both sides, but stronger activation on ipsilateral hemisphere to the robotic glove, which is contralateral to the hand executing the pinch movements.…”
Section: ) Activation Level (Hbo Concentration)mentioning
confidence: 97%